Cell division method for mobility analysis of multi-loop mechanisms. (November 2019) - Li, Chuanyang; Guo, Hongwei; Tang, Dewei; Liu, Rongqiang; Deng, Zongquan; Song, Xiaoke; Zahin, Sahad Imtiaz
Highlights: Cytology of mechanism (CM) is presented for mechanism analysis;. In CM, one KP, the combination of KPs, and a mechanism can be regarded as a cell;. Cell division method is proposed for mobility analysis of multi-loop mechanism;. Cell division method is applied in three cases and its correctness is verified. Ab s tract: This paper presents a combination of biological and screw theories for analyzing mechanisms, namely, cytology of mechanism (CM). In CM, kinematic pairs are considered as cells and they are the most important part of mechanisms. CM comprises four concepts, namely, cell division, cell division–differentiation, cell combination, and cell combination–variation. Consequently, mathematical models based on screw theory are employed to describe those concepts. A cell division method (CDM) is also proposed for mobility analysis of multi-loop mechanisms based on cell division. The basic principle of this method is to transform mobility analysis into constraint analysis between kinematic pairs and mobility analysis of parallel sub-mechanisms. Finally, CDM is used for analyzing the mobility of three typical multi-loop mechanisms to verify its correctness and practicality.